Cyrkulacja śladów Zagłady w polskim imaginarium – między stadionem a galerią sztuki - Kowalska-Leder, Justyna (Narracje o Zagładzie [czasopismo zamknięte], 2016)
Circulation of Tropes of the Shoah in Polish Imagery. Between a Stadium and an Art Gallery The starting point of this text, devoted to the circulation of tropes of the Shoah in Polish imagery, is Sławomir Buryła’s article, Topika Holokaustu. Wstępne rozpoznanie (2012). Instead of the research on the presence of loci communes of the Shoah in Polish literature, the author proposes the analysis of manifestations of traces of the Holocaust in contemporary Polish culture. The inspiration for such an approach is Barbara Skarga’s conception put forward in Ślad i obecność (2002). References to the Holocaust appear in various literary, cinematic and theatrical contexts, but also in journalism, Internet entries, street art and graffiti, and even chants sung in the stadium. They are driven by different intentions, their form reveals diverse cultural competencies, and yet they belong to one communication code. Therefore, an attempt at an analysis of tropes of the Holocaust in contemporary imaginary, in which communicative signs circulate despite class, regional or generational differences, seems to be legitimate, even if these tropes are not equally legible in all the situations and for all the people. Such an analytical work would include tracing their historical changes, but first of all it would make it possible to treat traces of the Holocaust as the tropes leading to the main problems of Polish identity narration and collective memory. Key words: trace, imagery, topos, Holocaust, narrative